Mengurai Benang Kusut Kesepian: Korelasi Antara Keyakinan Irasional Dan Kesepian Siswa - Sugara, Gian Sugiana; Nurfitriani, Sani; Imaduddin, Aam; Bariyyah, Khairul (Universitas Nusantara PGRI Kediri, 2023)
This study aims to describe the influence of irrational beliefs on loneliness in class VII MTSN 1 Tasikmalaya students. This research is a quantitative descriptive approach with a correlational design. The sample for this study amounted to 231 students of class VII MTSN 1 Tasikmalaya was taken using a simple random sampling technique. There are two instruments used in this study, UCLA Loneliness Scale Version 3 (20 items) and Attitude Belief Scale III (13 items). Data were analyzed using descriptive analysis and a simple linear regression. The findings for this study indicate that there is a significant influence between irrational beliefs on loneliness in teenagers at MTSN 1 Tasikmalaya. It can be said that irrational beliefs and loneliness have a fairly strong relationship, meaning that the higher the irrational beliefs, the higher the loneliness, and the lower the irrational beliefs, the lower the loneliness. Based on the results of this study, it is hoped that further research require treatment of students so that they have a rational mindset and have the right feelings, so that students can plan and carry out better, more productive and normative actions. One strategy that can be used to reduce loneliness is by providing guidance and counseling services with rational emotive behavior therapy based counseling with group counseling treatment.